Cutaneous mucormycosis postcosmetic surgery: A case report and review of the literature. Issue 27 (July 2016) - Al-Tarrah, Khaled; Abdelaty, Mahmoud; Behbahani, Ahmad; Mokaddas, Eman; Soliman, Helmy; Albader, Ahdi
Abstract: Background: Mucormycosis is a rare, aggressive, and life-threatening infection that is caused by organisms belonging to the order Mucorales. It is usually acquired through direct means and virtually always affects immunocompromised patients with the port of entry reflecting the site of infection, in this case, cutaneous. Unlike other mucormycoses, patients affected by Apophysomyces elegans (A elegans) are known to be immunocompetent. This locally aggressive disease penetrates through different tissue plains invading adjacent muscles, fascia, and even bone causing extensive morbidity and may prove fatal if treated inadequately. Cutaneous mucormycosis is associated with disruption of cutaneous barriers such as trauma. However, rarely, it may be iatrogenic. No cases have been previously reported postcosmetic surgery, especially one that is so commonly performed, lipofilling. Case Report: The patient is a, previously healthy, 41-year-old middle-eastern female who was admitted to the plastic surgery department 17 days after undergoing cosmetic surgery. She suffered from extensive tissue inflammation and necrosis in both gluteal regions. Following admission, she was initially started on empirical antimicrobial therapy which was changed to an antifungal agent, voriconazole, when preliminary microbiological results showed filamentous fungi. This was discontinued and liposomal amphotericin B was commenced when further mycological analysis identified A elegans . Furthermore, she underwent a total of 10 sessions of extensive debridement to the extent that portions of the sacrum and left femoral head became exposed. Her clinical status and wounds improved with the appropriate management and she remained an inpatient for 62 days. Subsequently, she had defects in both gluteal regions which required reconstructive surgery. Conclusion: A elegans is an uncommon cause of iatrogenic cutaneous mucormycosis. A high index of clinical suspicion is required, especially in the absence of clinical improvement despite conventional methods of treatment, so that early diagnosis can be reached and the appropriate management instigated promptly in order to mitigate morbidity and mortality. Reversal of predisposing risk factors, regular extensive surgical debridement, and antifungal therapy remain the cornerstones of therapy for this life-threatening condition.